2019
DOI: 10.12688/f1000research.15318.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding and management of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a multifaceted condition characterized by chronic anovulation and excess ovarian activity, in contrast to other causes of anovulation that involve ovarian dormancy or primary insufficiency. Recent studies indicated that PCOS is associated with low-grade chronic inflammation and that women with PCOS are at increased risk of non-alcoholic fatty liver disease. The inflammatory and metabolic derangements associated with PCOS are explained in part by the coexistence of insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 70 publications
0
58
0
7
Order By: Relevance
“…PCOS is a highly prevalent endocrine condition affecting 6% to 8% of women worldwide. It is characterized by ovulatory dysfunction and hyperandrogenism, which can confer a higher risk of female infertility [ 61 , 62 , 63 , 64 ]. In addition to reproductive abnormalities, PCOS is also linked to obesity, insulin resistance, dyslipidemia, diabetes, and cardiovascular diseases.…”
Section: Exosomes In the Pathophysiology Of Female Reproductionmentioning
confidence: 99%
“…PCOS is a highly prevalent endocrine condition affecting 6% to 8% of women worldwide. It is characterized by ovulatory dysfunction and hyperandrogenism, which can confer a higher risk of female infertility [ 61 , 62 , 63 , 64 ]. In addition to reproductive abnormalities, PCOS is also linked to obesity, insulin resistance, dyslipidemia, diabetes, and cardiovascular diseases.…”
Section: Exosomes In the Pathophysiology Of Female Reproductionmentioning
confidence: 99%
“…Remarkably, 5% to 10% of women 18-44 years of age have PCOS, making it the most common endocrine disorder among women of reproductive age. Recent investigations have shown that PCOS is linked to low-grade chronic inflammation [ 18 , 19 ]. Therefore, approaches to modulate the immune system and inflammatory pathways may be useful in treating PCOS.…”
Section: Female Reproductive System Disordersmentioning
confidence: 99%
“…Синдром полікістозних яєчників (СПКЯ)поширена ендокринна патологія з поліморфною етіологією, патогенезом і фенотиповими проявами, що чинить негативний вплив не лише на репродуктивну функцію, а й на стан вуглеводного, ліпідного обміну, функцію серцево-судинної системи, психічне здоров'я і підвищує ризик деяких онкопатологій протягом усього життя жінки та її потомства [1].…”
Section: вступunclassified